The development of ethnoscience-based e-student worksheets to enhance Students scientific literacy at Madrasah Ibtidaiyah - Wiratama, Rivaldi; Minarno, Eko Budi; Tharaba, M. Fahim (Mitra PGMI: Jurnal Kependidikan MI, 2025)
Science literacy is the ability to apply scientific knowledge in daily life, yet students' science literacy in Indonesia remains low. This study aims to develop ethnoscience-based electronic student worksheets (e-LKPD) and evaluate their feasibility, attractiveness, and effectiveness. The research uses the Research and Development (R&D) method with the ASSURE development model. The results show that the e-LKPD received validation from three experts: material experts (95.55%), design experts (91.66%), and learning practitioners (83.00%), all falling into the very valid category. The worksheets were found to be highly attractive, with a score of 85.21%. The N-Gain score was 0.79, indicating high effectiveness. The independent sample T-test revealed a significant difference in science literacy between the experimental and control classes (p = 0.001, less than 0.05). In conclusion, ethnoscience-based e-LKPD effectively enhances students' science literacy, as shown by the improvement from pretest to posttest results.